Association Between Obesity and Lower Urinary Tract Symptoms Among Children and Adolescents: A Community-Based Study - Wang, Shih-Gang; Yang, Stephen Shei-Dei; Chang, Shang-Jen (Frontiers in Pediatrics, 2021)
Introduction: Obesity is associated with lower urinary tract symptoms (LUTSs) and dysfunction in adults while its impact on children and adolescents remains unknown. This study aimed to explore the impact of obesity on LUTSs among children and adolescents through a large-scale community-based study. Methods: From July 2004 to April 2017, children and adolescents aged 5 to 15 years-old in Xin-Dian District, New Taipei City were invited to participate in our study. The exclusion criteria were a history of congenital genitourinary tract anomalies, neurological anomalies, or a presence of urinary tract infection. After providing informed consent the participant completed a questionnaire, which included their baseline characteristics and dysfunctional voiding symptom score (DVSS); a parent completed the questionnaire with the younger children. Urgency and daytime incontinence were defined as having positive statement for DVSS questions 7 and 1, respectively. Multivariate regression analysis was used to evaluate the predictors of urgency, daytime incontinence and enuresis. A p-value of <0.05 was considered statistically significant. Results: A total of 2,371 participants were enrolled in the study, and 1,599 were ultimately eligible for analysis. The prevalence of urgency, daytime incontinence, constipation and enuresis were 37.6%, 6.4%, 26.1%, and 7.7%, respectively. Multivariate analysis revealed that younger age (p=0.01) and obesity (p=0.04) were independent predictors for urgency. Younger age (p<0.01) and constipation (p=0.04) were independent predictors for daytime incontinence but obesity was not. Younger children were more likely to have nocturnal enuresis (95% CI=0.77-0.88) and obesity did not have a significant impact on enuresis. Conclusion: Obesity was significantly associated with urgency but it was not significantly associated with daytime incontinence and enuresis in community dwelling children and adolescents.